Harvard Law School year book. - Harvard University Phillips Brooks House Association. Year Book Committee (Cambridge, Mass. Year Book Committee of Phillips Brooks House Association of Harvard University, 1937)
Annual
None published, 1942/1943-1944/1945.
Title varies slightly.
Vols. for 1937/1938-1946/1947 called also v. 1-7.
Keywords: Harvard Law School -- Students